Edukasi Gizi Gaya Hidup Sehat Menuju Tubuh Ideal Impian Remaja di Harjomulyo Jember - Ervyanna, Ellanda Rima; Rahma Sari, Vadira; Septiani, Baiq Dewi Sukma; Fitriyah, Holif; Safitri, Erwina (Yayasan Inspirasi El Burhani, 2025)
Introduction: Adolescence is a transitional period from childhood to adulthood. Having an ideal body is the aspiration of many individuals, including adolescents. A healthy lifestyle is one of the approaches to achieving both an ideal and healthy body. However, limited understanding of nutrition often leads to unhealthy behaviors. Therefore, nutrition education is necessary to enhance knowledge and promote healthy practices. Objective: The aim of this activity was to increase public knowledge, particularly among adolescents, regarding healthy lifestyles, to improve their ability to select nutritionally balanced foods, and to enhance motivation for engaging in regular physical exercise. Method: This community service activity was conducted using a lecture method and was attended by 30 adolescents from Harjomulyo Village, Silo Subdistrict, Jember Regency. Data collection was carried out through pre-test and post-test questionnaires to assess the level of knowledge regarding healthy lifestyles before and after the provision of nutrition education. Result: The results of the pre-test and post-test showed that participants’ knowledge increased by 35.33%, rising from 56.67% to 92%. This outcome exceeded the predetermined target, indicating that the program was highly effective. Conclusion: Participants’s knowledge regarding healthy lifestyles improved significantly following the implementation of nutrition education.